A route efficiency analysis using Shannon entropy-based modified DEA method and route characteristics investigation for urban bus transport in India. Issue 3 (3rd July 2018) - Adhikari, Arnab; Basu, Sumanta; Biswas, Indranil; Banerjee, Ashim; Sengupta, Partha Pratim
ABSTRACT: In the context of urban bus transport, the efficiency study of the bus routes, the impact of the contextual factors on the efficiency, and environmental performance measurement have not been paid enough attention. For performance evaluation, scholars mostly apply conventional data envelopment analysis (DEA) model whose limitation regarding handling the undesirable parameter limits its usefulness in the presence of undesirable outputs. Here, we propose a Shannon entropy-based output-oriented consolidated DEA model for the holistic performance measurements of the bus routes. Apart from operational and financial performance measurement, we introduce a novel 'emission metric' for environmental performance assessment of the bus routes. We show the context-specific implementation of several modified DEA models for measuring the efficiencies of the bus routes and integrate the efficiencies from different models into a single score using Shannon entropy approach. We apply the proposed method on 21 bus routes of Kolkata, an urban city in India. Our method facilitates consistent and more improved score in case of profit-making and loss-making routes, respectively. According to our analysis, route length, route overlapping, number of intermediate stoppages, and cost structure play a crucial role in the performance. We provide several route-specific as well as policy-level recommendations.